In vitro microvascular actions of Artemisia vulgaries L. in a model of ischemia-referfusion injury in the rate of intestinal mesentery - Gumila, Elinor B.
This study investigates the microcirculatory anti-inflammatory effects of Artemisia vulgaris L. (damong maria) using the rat intestinal mesentery ischemia-reperfusion model. Previous studies have shown that A. vulgaris possesses general anti-inflammatory properties. Hemodynamic parameters (blood pressure, heart rate, micro vascular vessel diameters and leukocyte adhesion along the endothelium) observed for 10 minutes at baseline and after occlusion of the superior mesenteric artery were compared in 36 rats randomly assigned to the control group and treatment group. Prior to the conclusion, purified extract of A. vulgaris was given to the treatment group ( in = 17) while NSS was given to the control group (n = 19) intravenously. Monastral Blue B was also administered to both groups to detect endothelial leakage. Data was analyzed statistically using the Analysis of Variance for Repeated Measure and the Multivariate Analysis of Variance for Repeated Measures. Results showed that systolic blood pressure, diastolic blood pressure, and heart rate were unaltered after occlusion of the superior mesenteric artery and vein. In addition, there was a statistically significant decrease in the number of adherent leukocytes on the endothelial cells of postcapillary venules in the Artemisia vulgaris-treated group compared to the control group. The transendothelial leakage was also significantly lower in the treatment group than in the control group. In conclusion, ischemia-reperfusion of rat mesentery produces microcirculatory inflammatory events that are ameliorated by systematic administration of A. vulgaris purified extract.